Cerebellar contributions to persistent auditory verbal hallucinations in patients with schizophrenia - Cierpka, Maximilian; Wolf, Nadine D.; Kubera, Katharina Maria; Schmitgen, Mike; Wolf, Robert Christian (The cerebellum, 2017)
There is growing evidence that the cerebellum plays a crucial role in the pathophysiology of schizophrenia symptoms. Despite increasing evidence for cerebellar involvement in affective, attentive, and cognitive functions including language processing and perception, investigations of cerebellar contributions to auditory verbal hallucinations (AVH) in schizophrenia are lacking. Using structural magnetic resonance imaging at 3T, we investigated the data of 20 patients with schizophrenia and 14 matched healthy controls. Ten patients were classified as having chronic and treatment resistant AVH (pAVH), whereas the remaining ten patients either never had AVH in the past or were in full remission with regard to AVH (nAVH). Employing cerebellum-optimized segmentation techniques, i.e., the Spatially Unbiased Infratentorial Template (SUIT) toolbox, we investigated cerebellar gray matter volume (GMV) differences among the pAVH, nAVH, and a healthy control group, the magnitude of their expression between these groups and the relationship between GMV and schizophrenia symptom load. Lower GMV in pAVH patients compared to controls was found in lobules VIIb and VIIIa. Additionally, lower GMV in pAVH compared to nAVH patients was found in lobule VIIIa. A negative relationship between VIIIa GMV and overall positive symptoms was detected. Correlations with AVH-specific psychometric scores were not significant. This study shows that there are structural changes in the cognitive regions of the cerebellum that are linked to a clinical phenotype presenting with persistent positive symptoms such as AVH. The results suggest that the cerebellum and its associated neural circuits do play a role in the emergence of positive symptoms in schizophrenia, but probably not exclusively in AVH symptom expression.